Pengaruh Komitmen Organisasi, Penganggaran Partisipatif, Dan Kompetensi Pada Kinerja Manajerial Penyelenggara Pemerintahan Desa - Intan Pratiwi, Luh Made; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p03, 2019)
The aims of this study is to know determine the effect of the influence of organizational commitment, participatory budgeting ,and competence on managerial performance of village goverment administrators.  This research was conducted in 13 villages in Klungkung Regency.  The respondents used were 65 people who were determined by the probability sampling method, namely cluster random sampling. The data analysis technique uses multiple linear regression tests. The results showed that organizational commitment, participatory budgeting and competence simultaneously had a significant positive effect on managerial performance of village government administrators. Partial organizational commitment has a positive effect on managerial performance. Participatory budgeting partially has a positive effect on managerial performance. Competence also partially has a positive effect on managerial performance. Keywords :  Managerial performance, commitment, budgeting, competence.